FAILURE CASE STUDY OF SKF 6005 CARRIER IDLER BEARING - Erinofiardi, Erinofiardi; Suryono, Ahmad F; Sitohang, Noverson T (UNIB Press, 2019)
A conveyor idler belt is to serve as buffer in a transportation system of coal from the land to a ship the carrier of coal. The idler was loaded by 700 tons per hour. From the simulation, the bearing on the slant has a maximum value of von mises stress is 258.05 MPa by the crushed bituminous coals load, 340.09 MPa by the crushed anthracite coal, 528.26 MPa by crushed bituminous coals impact loads, 692.28 MPa by the crushed anthracite coal impact loads. The bearing age for crushed bituminous coals transportation is 278.81 days for 21 hours per day of service hour and 117.44 million round revolution; 139.6 days for the crushed anthracite coal and 58.81 million round revolution; however the pads located on the bottom right of transfer chute has a very short life of 22.62 days and 9.53 million round revolution for the crushed anthracite coal transportation and 47.24 days for crushed bituminous coal transportation and 19.9 million round revolution. The crack type of bearing was macro crack, pear skin, discoloratioan, wear, smearing, and corrosion. Periodic maintenance was necessary keeping the bearing longer in service life.